Pengaruh Implementasi Prinsip Syariah dalam Produk Pembiayaan Murabahah Bank Syariah Terhadap Kinerja Keuangan UMKM: Kajian Literatur - Rindyi Putri Lestari; Fauzatul Laily Nisa (CV. ALIM'SPUBLISHING, 2024)
Murabaha financing is one of the Islamic financing products that is popular among MSMEs. This product is in accordance with Islamic sharia principles which prohibit usury and encourage fair buying and selling transactions. This study aims to analyze the implementation of sharia principles in murabahah financing products of Islamic banks on the financial performance of MSMEs. A literature review was conducted to understand the concepts of sharia principles, murabaha financing, and MSMEs financial performance. Data were collected from various sources, journals, including books, and other reliable sources. The study results show that the implementation of sharia principles in murabaha financing products of Islamic banks has a positive influence on the financial performance of MSMEs. This positive influence can be seen from the increase in profitability and operational efficiency of MSMEs. In addition, murabaha financing can also help MSMEs to increase access to capital and develop their business.